Monotheism in the New Religious Movements of Japan: Historical and Taxonomical Challenges in Western Studies - Chandler, Kegan (Department of Religious Studies, 2024)
The study of Japan's New Religious Movements (NRMs) has long been a preoccupation of Western scholars. However, significant disagreement and confusion has existed in the West over whether some of these movements, exemplified in this study by Kurozumikyō, Tenrikyō, and Konkōkyō, are monotheistic or not. Scholars have alternatively described these NRMs as “polytheistic,” “monotheistic,” or “pantheistic,” while some have attempted to straddle multiple categories at once, or have treated these movements as entirely sui generis. This thesis, focusing on Western studies, argues that this long history of Western dissonance is the result of a complex layering of taxonomical, socio- cultural, and academic issues, including too-narrow definitions of monotheism, nationalistic discourse in Japan, scholarly avoidance of “Western” terminology and concepts, essentializing East-West dichotomies which emphasize “Japanese polytheism” and “Western monotheism,” and scholarly assumptions about devotional practices. This thesis begins to address this classificatory impasse by first expanding on recent advancements in the taxonomy of religion, including a definition of monotheism that takes into account its nuances and includes new monotheistic subcategories, and then by revisiting the teachings of Kurozumikyō, Tenrikyō, and Konkōkyō through this interpretive lens. In addition to problems of categorization, this thesis also contributes to the resolution of issues related to the historical development of monotheism in the NRMs. On an assumption that premodern Japanese religion offered NRM founders no trace of monotheism, some Western scholars have concluded that the emergence of NRM monotheism must be owed to contact between the founders and Kakure Kirishitan (Hidden Christians). This thesis conducts a new historical investigation in light of the new taxonomy, ultimately revealing several more plausible Japanese, non-Christian sources of monotheism in the history of Japanese religion. These findings indicate the need for a reformation of the image of monotheism in Western studies of Japan.